Innovation and Creativity Marketing Product on Social Media - Prayoga, Inggar; Fridayani, R Y (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose this research is to find out the impact of using social media in implementing marketing strategies. The research method used in this research was descriptive qualitative method analysis approach and literature review. This research focuses on social media, consumer patterns, and marketing strategies. The results of this research proved that using social media for business people is very important, besides that social media was considered to be effective and efficient for marketing products.